2006
DOI: 10.1155/mi/2006/78380
|View full text |Cite
|
Sign up to set email alerts
|

The Levels of Ghrelin, Leptin, TNF‐α, and IL‐6 in Liver Cirrhosis and Hepatocellular Carcinoma due to HBV and HDV Infection

Abstract: Background/Aim. Malnutrition, a common problem in liver cirrhosis and HCC, may readily deteriorate the clinical functions with resultant poor prognosis. Beside the hyper catabolic state frequently encountered in chronic liver disease and HCC, anorexia and reduced food intake also worsen the malnutrition. The recently discovered peptide hormone ghrelin acts as a counterpart of leptin in regulation of food intake and fat utilization. The aim of the present study was to investigate the ghrelin and leptin levels i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
82
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 50 publications
12
82
0
1
Order By: Relevance
“…HCC commonly arises in the liver with chronic inflammation (10,21). In the liver, the levels of TNF␣, a proinflammatory stimuli, in patients with cirrhosis and HCC have been reported to be significantly higher than those in normal individuals (22). Therefore, the cell growth of phosphorylated HSP27-overexpressed HuH7 cells was examined both in the presence and in the absence of TNF␣.…”
Section: Expression Of Hsp27 Inmentioning
confidence: 99%
“…HCC commonly arises in the liver with chronic inflammation (10,21). In the liver, the levels of TNF␣, a proinflammatory stimuli, in patients with cirrhosis and HCC have been reported to be significantly higher than those in normal individuals (22). Therefore, the cell growth of phosphorylated HSP27-overexpressed HuH7 cells was examined both in the presence and in the absence of TNF␣.…”
Section: Expression Of Hsp27 Inmentioning
confidence: 99%
“…In fact, most of the leading studies on the correlation between metabolic disturbances and ghrelin have focused on the estimation of total ghrelin (10,11,(13)(14)(15), and there are concerns about the specificity of available acylghrelin assays (17). We focused on measuring total ghrelin, with the aim of comparing our data with the discrepant total ghrelin levels that have been found in hepatic failure patients in different studies (18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to this finding, a study demonstrated that serum ghrelin levels were lower in patients with colorectal carcinoma compared with healthy controls, and patients with end-stage disease had lower ghrelin levels (24). Serum levels of active ghrelin were significantly higher in patients with prostate (18), ovarian (10), and hepatocellular carcinoma (11). Major hyperghrelinemia was observed in end-stage well-differentiated neuroendocrine carcinomas (25).…”
Section: Resultsmentioning
confidence: 93%
“…Circulating ghrelin levels were demonstrated as higher in a range of cancer types including colon cancer (8), prostate carcinoma (9), ovarian carcinoma (10), and hepatocellular carcinoma (11) however, no studies have evaluated serum ghrelin levels in papillary thyroid carcinoma. We aimed to investigate serum levels of ghrelin…”
Section: Introductionmentioning
confidence: 99%